2019
DOI: 10.1007/s00018-019-03152-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AMPK activity by type 10 adenylyl cyclase: contribution to the mitochondrial biology, cellular redox and energy homeostasis

Abstract: The downregulation of AMP-activated protein kinase (AMPK) activity contributes to numerous pathologies. Recent reports suggest that the elevation of cellular cAMP promotes AMPK activity. However, the source of the cAMP pool that controls AMPK activity remains unknown. Mammalian cells possess two cAMP sources: membranebound adenylyl cyclase (tmAC) and intracellularly localized, type 10 soluble adenylyl cyclase (sAC). Due to the localization of sAC and AMPK in similar intracellular compartments, we hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
(84 reference statements)
1
21
0
Order By: Relevance
“…In agreement with this study, we have recently revealed that sAC knockdown leads to a significant down-regulation of mitochondrial clearance in cardiac and endothelial cells [ 74 ]. These effects were associated with reduced lysosomal acidification and autophagosome accumulation (unpublished data), indicating disturbed autophagy flow due to lysosomal dysfunction.…”
Section: Role Of Sac In Lysosomal Functionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with this study, we have recently revealed that sAC knockdown leads to a significant down-regulation of mitochondrial clearance in cardiac and endothelial cells [ 74 ]. These effects were associated with reduced lysosomal acidification and autophagosome accumulation (unpublished data), indicating disturbed autophagy flow due to lysosomal dysfunction.…”
Section: Role Of Sac In Lysosomal Functionsupporting
confidence: 89%
“…Since V-ATPase leads to acidification of both endosomes and lysosomes, suppression of sAC, and, in turn, V-ATPase activity, may impair autophagy due to lysosomal dysfunction. Our recent studies support this idea by demonstrating that sAC inhibition or knockdown disturbs mitophagy in endothelial and cardiac cells [ 74 ], reduces lysosomal acidification, and leads to autophagosome accumulation (unpublished data). Furthermore, several studies have demonstrated the positive effects of cAMP elevation on the autophagy machinery [ 77 , 79 , 80 ].…”
Section: Role Of Sac In Autophagymentioning
confidence: 58%
“…Our recent report [66] showed a direct link between sAC and mitophagy in cardiac and endothelial cells. Particularly, downregulation of sAC led to the disturbed mitochondrial clearance that culminated in oxidative stress and energy imbalance.…”
Section: Sac and Mitophagymentioning
confidence: 87%
“…BioMed Research International energy balance in the cell [50]. In our model, both FSK induce overexpression of both AC and AMPK in adipose tissue of dyslipidemic rats.…”
mentioning
confidence: 89%